Can treatment of posterior malleolus fractures with tibio-fibular instability be usefully addressed by Bartonicek classification?. Issue 1 (January 2022) - Maluta, T.; Samaila, E.M.; Amarossi, A.; Dorigotti, A.; Ricci, M.; Vecchini, E.; Magnan, B.
Highlights: Bartonicek posterior malleolus fracture classification correlates with clinical outcomes. Ankle dislocation is associated with early post-traumatic arthritis. Conservative treatment in Bartonicek I–II has good clinical results. Surgical treatment is indicated for Bartonicek IV and displaced type III fracture. Abstract: Introduction: Ankle fractures account for 4% of all fractures and treatment of those involving the Posterior Malleolus remains controversial. Clinical and radiological outcomes in a cohort of patients with Posterior Malleolus fractures conservatively treated were retrospectively evaluated; furthermore, a treatment algorithm was suggested. Methods: Patients were divided according to Bartoníček classification. The clinical evaluation was made with OMAS/AOFAS scores; the radiological evaluation with Van Dijk classification for post-traumatic arthritis. Results: Clinical outcome worsened with the severity of Bartoníček classification, but early degenerative changes were not correlated neither to the clinical outcome nor to the injury pattern. Clinical and radiological outcomes depended on the damage of the syndesmosis as articular step-offs and tibio-fibular notch involvement. Discussion: We recommend conservative treatment for Bartoníček type I, type II and type III fractures, the latter when undisplaced and without tibial plafond depression. We suggest surgical treatment for type IV and displaced type III fractures.